A Novel Aqueous Zinc‐Ion Hybrid Supercapacitor Based on TiS2 (De)Intercalation Battery‐Type Anode. (13th August 2020) - Wang, Qiang; Wang, Siliang; Li, Jiayi; Ruan, Limin; Wei, Ning; Huang, Linsheng; Dong, Ziyan; Cheng, Qinghua; Xiong, Yi; Zeng, Wei
Abstract: The recent research on aqueous zinc‐ion hybrid supercapacitors (ZHSCs) based on zinc metal anode has attracted great attention in energy storage systems due to the inherited merits of supercapacitors and batteries. However, the problems of sluggish diffusion of zinc ion, low utilization rate of zinc foil, and uncontrollable zinc dendrites limit the application of ZHSCs. In order to effectively solve the above problems, a ZHSC is constructed and investigated with a 2D layered titanium disulfide (TiS2 ) (de)intercalation battery‐type anode and an active carbon (AC) capacitor‐type cathode in 2 m ZnSO4 electrolyte. Notably, this ZHSC demonstrates a high specific capacitance of 249 F g −1 (0.2 A g −1 ), a superior energy density of 112 Wh kg −1 (180 W kg −1 ), and a high power density of 3600 W kg −1 (35 Wh kg −1 ) based on the total weight of the anode and cathode active materials. Furthermore, the ZHSC also shows long service life with a capacitance retention of 92% after 5000 cycles at a current density of 2 A g −1 . This work provides a concept to design next‐generation high‐performance ZHSC by replacing the zinc foil anode with a (de)intercalation battery‐type anode. Abstract : A zinc‐ion hybrid supercapacitor (ZHSC) assembled with a 2D‐layered titanium disulfide (TiS2 ) (de)intercalation battery‐type anode and an active carbon capacitor‐type cathode in 2 m ZnSO4 electrolyte exhibits excellent electrochemical performance.